Polska zdekolonizowana? „Pamięć o kobietach” i jej wymiary - Kania, Eliza (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
What is the meaning of „herstory” concept? Can gender perspective be useful to discuss the dimensions of historical narratives? The text is an attempt to answer questions concerning the historical and cultural contexts of showing women’s role in history. It also analyses the content of crucial publications due to which the discussion on using gender perspective in historical narratives in Poland has begun.